Ligand-free MnBr2-catalyzed chemo- and stereoselective hydroboration of terminal alkynes - Pawar, Rameshwar B.; Karmur, Mital H.; Punji, Benudhar (Chemistry-an asian jounrnal, 2024)
Developing simple and benign protocols for synthesizing alkenylboronates is crucial as they are synthetically valuable compounds in various organic transformations. In this work, we report a straightforward ligand-free protocol for synthesizing alkenylboronates via atom-economical hydroboration of alkynes with HBpin catalyzed by a manganese salt. The reaction shows a high level of chemo and regioselectivity for the terminal alkynes and exclusively produces E-selective alkenylboronates. The hydroboration scope is vast, with the resilience of a range of synthetically beneficial functionalities, such as halides, ether, alkenyl, silyl and thiophenyl groups. This reaction proceeds through the involvement of a metal-hydride intermediate. The developed alkenylboronate can be smoothly converted to useful C-C, C-N and C-I bond-forming reactions.
Keywords: alkenylboronates; alkyne; Hydroboration; manganese; stereoselectivity